Evaluating potential conservation conflicts between two listed species: sea otters and black abalone - Peter Raimondi; Laura J. Jurgens; M. Tim Tinker (Ecology, 2015)
Population consequences of endangered species interacting as predators and prey have been considered theoretically and legally, but rarely investigated in the field. We examined relationships between spatially variable populations of a predator, the California sea otter, Enhydra lutris nereis , and a prey species, the black abalone, Haliotis cracherodii . Both species are federally listed under the Endangered Species Act and co‐occur along the coast of California. We compared the local abundance and habitat distribution of black abalone at 12 sites with varying densities of sea otters. All of the populations of abalone we examined were in the geographic area currently unaffected by withering disease, which has decimated populations south of the study area. Surprisingly, our findings indicate that sea otter density is positively associated with increased black abalone density. The presence of sea otters also correlated with a shift in black abalone to habitat conferring greater refuge, which could decrease illegal human harvest. These results highlight the need for a multi‐species approach to conservation management of the two species, and demonstrate the importance of using field‐collected data rather than simple trophic assumptions to understand relationships between jointly vulnerable predator and prey populations.